Effect of high voltage atmospheric cold plasma on extraction of fenugreek galactomannan and its physicochemical properties. (December 2020) - Rashid, Farhat; Bao, Yiwen; Ahmed, Zaheer; Huang, Jen-Yi
Graphical abstract: Highlights: Fenugreek seeds treated with cold plasma showed apparent surface ruptures. Cold plasma treatment largely increased extraction yield of fenugreek galactomannan. Plasma-treated galactomannan had higher water binding capacity, swelling index and apparent viscosity. Cold plasma treatment had insignificant effect on molecular and crystalline structures of galactomannan. Abstract: Fenugreek is a good source of galactomannan, however, conventional methods for its extraction are generally time-consuming and have relatively low recovery rates. In this study, we applied high voltage atmospheric cold plasma (HVACP) as a pretreatment and investigated its effects on galactomannan extraction from dry fenugreek seeds and soaked seeds in NaCl solution, as well as its physicochemical properties. Results showed that HVACP treatment with air at 80 kV for 30 min caused apparent structural disruption on fenugreek seed surface and decreased the pH of extracting solution, resulting in increased galactomannan extraction yields, by 122% from soaked seeds and 67% from dry seeds. Galactomannan treated with HVACP had higher water-binding capacity, swelling index and viscosity, as well as lower melting enthalpy. HVACP treatment also altered the surface morphology of galactomannan due to plasma etching, but no significant changes in its molecular and crystalline structures were observed. The findings of this study prove that HVACP can be a green approach, in terms of reduced chemical use, to effectively enhance the extraction efficiency of fenugreek galactomannan and modify its functional properties, hence facilitate more diverse applications in both food and polymer industries.